2010
DOI: 10.15288/jsad.2010.71.704
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Indicators Predict Results of an Informed-Consent Quiz Among Substance-Dependent Treatment Seekers Entering a Randomized Clinical Trial

Abstract: ABSTRACT. Objective: This study sought to determine the extent to which key aspects of a clinical trial's protocol were recalled by participants entering a clinical trial for alcohol and illicit substance-use treatment after standard informed-consent procedures, as well as to explore the possible relationships between recall, neuropsychological functioning, and substance-use outcomes. Method: Before entering a randomized clinical trial testing the effectiveness of a computer-based training version of cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 40 publications
3
11
0
Order By: Relevance
“…Our study participants’ mean CQ score of 89.0% is consistent with the consent quiz scores from the two most directly comparable studies, both of which used a True/False quiz with a substance-dependent, though not necessarily CJS-involved population; their average scores were 90% ( SD =10.6) and 87.1% ( SD =9.2) respectively (Harrison et al, 1995; Kiluk et al, 2010). Not surprisingly, scores from our study are higher than those measured using open-ended consent quizzes (Table 2).…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Our study participants’ mean CQ score of 89.0% is consistent with the consent quiz scores from the two most directly comparable studies, both of which used a True/False quiz with a substance-dependent, though not necessarily CJS-involved population; their average scores were 90% ( SD =10.6) and 87.1% ( SD =9.2) respectively (Harrison et al, 1995; Kiluk et al, 2010). Not surprisingly, scores from our study are higher than those measured using open-ended consent quizzes (Table 2).…”
Section: Resultssupporting
confidence: 79%
“…Having information about which consent quiz items are frequently answered incorrectly can also help researchers determine which aspects of their informed consent process should be revised or given more attention. Although not ideal for ascertaining depth of understanding (MacQueen et al, 2014; Tam et al, 2015), True/False or multiple choice instruments are commonly used to test knowledge given their efficiency and ease of use particularly when assessing on a large-scale (Grady et al, 2017; Kiluk et al, 2010; MacQueen et al, 2014; Rounsaville et al, 2008; Tam et al, 2015) and we argue they are likely to be used if consent quizzes are widely adopted as a screening tool or prerequisite to study entry. For situations in which investigators want further assurance that information can be brought to mind by participants without the external prompt provided by closed-ended question formats, open-ended methods such as teach-back are useful, although more time is required.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies assess understanding in the informed consent process within vulnerable populations (Agre and Rapkin, 2003; Rosen et al, 2015), showing that lower levels of education and cognitive performance correlate with lower comprehension test scores in adult patients with psychotic disorders or SUD (Dunn and Jeste, 2001; Kiluk et al, 2010). This evidence does not suggest that persons with psychiatric disorders or lower literacy are incapable of providing informed consent (Davis et al, 2006; Misra et al, 2008; Hickman et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, comorbid psychopathology (i.e. impulsivity and alcohol use; (de Wit, 2009; Potenza, 2007), cognitive impairment, and educational attainment (McCrady & Bux Jr, 1999) may inhibit comprehension of study procedures among substance users (Kiluk, Nich, & Carroll, 2010). It should be noted that 67% of adolescents entering SUD treatment reported criteria for one or more psychiatric disorders, such as conduct disorder, attention deficit hyperactivity disorder, depression, and generalized anxiety disorder (Dennis, White, & Ives, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kiluk et al, (2010) investigated neurocognitive predictors of AQE among adults seeking outpatient substance use treatment. Results showed that 85% of participants made at least one AQE, with AQE significantly associated with intelligence, attention, and frequency of substance use.…”
Section: Introductionmentioning
confidence: 99%